The Voxel Mice Model of MCNPX for Simulation In Vivo Test BNCT - Agung Prastowo; Yohannes Sardjono; Widarto Widarto (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
A study of voxel mice model of MCNPX has been done for in vivo test Boron Neutron Capture Therapy (BNCT). Mathematical and parameters were used to construct the stylized Mice model phantom. The geometry was modified into simulation software MCNPX (Monte Carlo N-Particle eXtended) simulation input. The result of mice stylized model phantom has been showed Figure 3.